Maternal Socioeconomic, Demographic and Nutritional Factors Contributing to Improve Low Birth Size in Bangladesh - Hossain, Tazia (International Journal For Research In Mathematics And Statistics, 2021)
Though the child and infant mortality is decreasing for the last few decades, levels of infant and child mortality and morbidity in many developing countries including Bangladesh is still unacceptably high. Low birth weight is a significant indicator to premature birth, neonatal and infant mortality and associated with child development. The objective of the study is to evaluate impact of maternal socio-economic, demographic and nutritional (iron tablets) factors on the low birth size. For the analysis of birth size status of child, binary logistic regression model is applied. Number of antenatal visit during pregnancy, wealth index, birth order, and child is twin and mother’s education found significant for birth size status. . This study recommend that selectively targeted interventions such as antenatal visit (at least 3 visit during pregnancy), delay age at first pregnancy (at >20 year of age), improving maternal education and nutrition, iron and vitamin supplementation can prevent low birth size in Bangladesh. Sex of child, preceding birth intervals and religion are observed insignificant but consistent with the expectation to reduce low birth size. This study suggests the strategy to reduce low birth size by increasing antenatal visits during pregnancy and focusing on nutrition education, taking iron & vitamins supplementation during pregnancy along with discouraging teenage pregnancy.